Indole-3-carbinol ameliorated the neurodevelopmental deficits in neonatal anoxic injury in rats - Ramakrishna K.; Krishnamurthy S. (My University, 2025)
Neonatal anoxia is linked to long-lasting neurodevelopmental deficits. Due to the lack of pharmacological intervention to treat neonatal anoxia, there is interest in finding new molecules for its treatment. Indole-3-carbinol (I3C) has shown neuroprotective effects in some disease conditions. However, the neuroprotective role of I3C in neonatal anoxia has not been explored. Consequently, we have investigated the effect of I3C on neonatal anoxia-induced brain injury and neurodevelopmental deficits. Rat pups after 30 h of birth were subjected to two episodes of anoxia (10 min in each) at a time interval of 24 h by flowing 100% nitrogen. I3C was administered within 30 min of the second episode of anoxia on a postnatal day (PND) 3 and continued for PND 9. Neurodevelopmental deficits, cortical mitochondrial membrane potential (MMP), opening of mitochondrial permeability transition pore (MPTP), electron transport chain (ETC) enzyme activities, oxidative stress, hypoxia-inducible factor-1α (HIF-1α) levels, histopathological changes, and apoptosis were measured. I3C treatment dose-dependently ameliorated the neurodevelopmental deficits and somatic growth in anoxic pups. I3C improved mitochondrial function by enhancing the MMP, mitochondrial ETC enzymes, and antioxidants. It blocked the MPTP opening and release of cytochrome C in anoxic pups. Further, I3C reduced the elevated cortical HIF-1α in neonatal anoxic pups. Furthermore, I3C ameliorated histopathological abnormalities and mitochondrial-mediated apoptotic indicators Cyt C, caspase-9, and caspase-3. Our study concludes that I3C improved neuronal development in anoxic pups by enhancing mitochondrial function, reducing HIF-1α, and mitigating apoptosis. © 2022 International Society for Developmental Neuroscience.